2016
DOI: 10.1007/s11356-016-7048-8
|View full text |Cite
|
Sign up to set email alerts
|

Reductions of bacterial antibiotic resistance through five biological treatment processes treated municipal wastewater

Abstract: Wastewater treatment plants are hot spots for antibiotic-resistant bacteria (ARB) and antibiotic resistance genes (ARGs). However, limited studies have been conducted to compare the reductions of ARB and ARGs by various biological treatment processes. The study explored the reductions of heterotrophic bacteria resistant to six groups of antibiotics (vancomycin, gentamicin, erythromycin, cephalexin, tetracycline, and sulfadiazine) and corresponding resistance genes (vanA, aacC1, ereA, ampC, tetA, and sulI) by f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(16 citation statements)
references
References 47 publications
2
14
0
Order By: Relevance
“…Higher NH 4 + -N concentration was found to lead to lower removal of iARGs at the same chlorine dosage. Yuan et al (2016) reported that the purification of wastewater quality parameters (COD, NH + -N and turbidity) exhibited a positive correlation with ARB and ARGs reductions during the treatment in UWWTP. However, TN, TP and COD of influent, temperature and conductivity of mixed liquor were significant (p<0.05) correlated to multiple ARGs distribution in MBRs (Sun et al, 2016).…”
Section: Mmentioning
confidence: 97%
“…Higher NH 4 + -N concentration was found to lead to lower removal of iARGs at the same chlorine dosage. Yuan et al (2016) reported that the purification of wastewater quality parameters (COD, NH + -N and turbidity) exhibited a positive correlation with ARB and ARGs reductions during the treatment in UWWTP. However, TN, TP and COD of influent, temperature and conductivity of mixed liquor were significant (p<0.05) correlated to multiple ARGs distribution in MBRs (Sun et al, 2016).…”
Section: Mmentioning
confidence: 97%
“…Specific biological treatment processes are highly variable, from suspended floc growth in the case of standard activated sludge treatment to attached biofilm processes, and mixed aerobic and anaerobic stages for biological nutrient removal. Following primary treatment, the water still contains some raw-sewage associated bacteria and several field studies have been conducted tracking ARB and ARGs through various biological treatment processes [68,101,102]. General log removal value (LRV) of bacteria following biological treatment is typically around 1-log, while the specific effects on ARB and ARGs are relatively more varied, which may be reflective of the nature of the sewage, process performance, climatic and unknown factors.…”
Section: Treatment Technologies To Remove Arb and Argsmentioning
confidence: 99%
“…The conditions in WWTPs, including the mixture of organisms from diverse environmental origins and the availability of surfaces and biofilms, can create strong selection pressures for resistance [ 8 , 17 ]. Even those treatments that are effective in removing bacteria from the water can promote the exchange, selection, and dispersal of genes involved in antibiotic resistance [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%